2013
DOI: 10.1080/07294360.2013.841642
|View full text |Cite
|
Sign up to set email alerts
|

Local university students and intercultural interactions: conceptualising culture, seeing diversity and experiencing interactions

Abstract: This paper examines the intercultural interaction experiences of local, first-year students (n=25) in their first few weeks at university. The focus on local students complements existing intercultural interaction literature, which has tended to concentrate on the experience of the 'cultural other' student. Employing qualitative analysis, the study revealed relationships between how students conceptualise culture, see diversity and experience their initial intercultural interactions on campus. A link between s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 33 publications
2
19
0
Order By: Relevance
“…These findings support, in general terms, those of Sweeney, Weaven and Herington (2008), Popov et al (2012) and Colvin, Volet and Fozdar (2014), who all found differences in perspectives among international students from different countries. In terms of the UK findings in our study, they could be in line with those of Harrison and Peacock (2010), who found that home students (i.e.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…These findings support, in general terms, those of Sweeney, Weaven and Herington (2008), Popov et al (2012) and Colvin, Volet and Fozdar (2014), who all found differences in perspectives among international students from different countries. In terms of the UK findings in our study, they could be in line with those of Harrison and Peacock (2010), who found that home students (i.e.…”
Section: Discussionsupporting
confidence: 81%
“…Very little attention has been paid to the impact of level of study (undergraduate/ postgraduate) or to the potential differences among the extremely large category 'international students'. It is particularly important that the latter is taken into account, because several recent studies (Sweeney, Weaven and Herington 2008;Popov et al 2012;Colvin, Volet and Fozdar 2014) have mentioned this issue. For instance, Sweeney, Weaven and Herington (2008, 125), in their focus group study, report as follows:…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…This is supported by other studies reporting that the reticence of home students to build relationships with international students is not universal and that a substantial minority have more positive attitudes. Colvin, Volet and Fozdar (2014) establish a contrast between home students with a constructivist worldview, grounded in ethnorelativism and heterogeneous perceptions of diversity, and those whose experience of intercultural interactions is essentialist, shallow, ethnocentric and segregating. In particular, the latter group were marked by a strong belief in rigid cultural boundaries and homogeneity, often built around strong stereotypes.…”
Section: Scope Of Reviewmentioning
confidence: 99%
“…The reason why total percentage of some items were not 100 was because participants did not put check -mark on any option of these items. 5. Intercultural awareness in course design It was found from Table6 that the participants mostly agreed that culture should be part of language course and integrated into language teaching (87.7%).…”
Section: A Results and Quantitative Data Analysismentioning
confidence: 99%